Neomarica castaneomaculata and N. involuta (Iridaceae): two new endemic species from the Atlantic Forest, Brazil - Oliveira, Pâmela Novais De; Gil, André Dos Santos Bragança; Giulietti, Ana Maria; Oliveira, Reyjane Patrícia De; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2016)
Based on field studies, herbarium specimens and cultivated plants, two new species of Neomarica, collected in the states of Bahia, Espírito Santo, Rio de Janeiro and Minas Gerais, are described. Neomarica castaneomaculata differs from all other known species of the genus by the presence of a conspicuous triangular chestnut colored spot at the apex of the inner tepals, as well as a combination of other vegetative and floral characters. Neomarica involuta can be distinguished from other species by the conspicuously involute apical inner tepals margins. Illustrations, distribution maps and a commentary on morphology, taxonomic relationships and the conservation status of the new species are also provided.